The Congruence of Factor-Analytic Structures: Comparisons of Four Procedures and Their Solutions - Golembiewski, Robert T.; Billingsley, Keith; Yeager, Samuel (Academy of Management Review, 1976)
Use of factor analytic techniques for the analysts of organizational data is increasing. Four readily available techniques are described. Results derived from application of each technique to a common data set are compared.